PERANAN PATA (PACIFIC ASIA TRAVEL ASSOCIATION) DALAM MENINGKATKAN WISATAWAN ASIA PASIFIK DI BALI 2007-2013 - Yenny Nutrician Tampubolon; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes the role of PATA (Pacific Asia Travel Association) as organization non governmental in assisting restore post-Bali. Balinese have the most revenue from tourism. However, in the aftermath of the Bali bombing terrorism case of 2002 and 2005 caused a decline in the income of local communities because of the crisis visitors. This research applies qualitative research method. Data in this research in taken from books, journals, internet, media, and reference sharing. This research uses the pluralism perspective, role theory and non-govermental organization concept.This result from this research founsd that the PATA Bali in partnership with governments and other tourism organizations and have a responsibility to promote Bali tourism after the issue of terrorism. PATA seeks to restore the image of Bali as The Island of Paradise for the world intrenasional and still make tourism in Bali as a tourist destination for local and foreign tourists.Keyword : Bali tourism, NGO, Asia Pacific, terrorism